Small-cell neuroendocrine carcinoma of the larynx. A case report. - Da Silva, Dinis Paulo Antunes (2018)
The authors present a case of small cell neuroendocrine carcinoma of the larynx. The literature was reviewed in relation to the clinical, diagnostic and therapeutic aspects of this very rare tumor.